(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2013)
The special resource resolution procurement is the goal or the ultimate purpose of this procedure, and is therefore vital to its study, since it has a number of features and peculiarities, such as the system of appeals established against it, that determine the need to deep in its study in the light of the resolutions of the various administrative bodies responsible for the resolution of special resource procurement, especially the Public Procurement Administrative Tribunal of the Community of Madrid.